Satirical content on social media platforms - An analytical study of a sample of the satirical videos of the Zanga Crazy group on the TikTok application - AOUAD, Salaheddine; AIT KACI, Dhahbia (Social Sciences Journal)
This study attempts to shed light on the phenomenon of satirical content across social media platforms by addressing the most important basic points about the concept of satire and the methods of its creation and production across virtual sites, by selecting videos on the TikTok application for the Zanga Crazy group as a group active in the production of satirical content in Algeria. This is to apply the content analysis method to three selected videos for three different Algerian issues: a social issue, a sports issue, and an economic issue, relying on the content analysis form for the study sample. The study concluded that satirical content has become a widespread phenomenon across social media, especially on the TikTok application, in addition to the fact that the videos selected for the study sample highlight the great ability to convey the idea of ​​the content in a funny, satirical way, but it carries meanings for the lived Algerian reality